Anesthetic Cardioprotection in Clinical Practice From Proof-of-Concept to Clinical Applications - Zaugg, Michael; Lucchinetti, Eliana; Behmanesh, Saeid; S. Clanachan, Alexander (Current Pharmaceutical Design, 2014)
In 2007, the American Heart Association (AHA) recommended (class IIa, level of evidence B) in their guidelines on Perioperative Cardiovascular Evaluation and Care for Noncardiac Surgery volatile anesthetics as first choice for general anesthesia in hemodynamically stable patients at risk for myocardial ischemia. This recommendation was based on results from patients undergoing coronary artery bypass grafting (CABG) surgery and thus subject to criticism. However, since a “good anesthetic” often resembles a piece of art in the complex perioperative environment, and is difficult to highly standardize, it seems unlikely that large-scale randomized control trials in noncardiac surgical patients will be performed in the near future to tackle this question. There is growing evidence that ether-derived volatile anesthetics and opioids provide cardioprotection in patients undergoing CABG surgery. Since 2011, the American College of Cardiology Foundation/AHA have recommended a “volatile-based anesthesia” for these procedures (class IIa, level of evidence A). It is very likely that volatile anesthetics and opioids also protect hearts of noncardiac surgical patients. However, age, diabetes and myocardial remodeling diminish the cardioprotective benefits of anesthetics. In patients at risk for perioperative cardiovascular complications, it is essential to abandon the use of “anti-conditioning” drugs (sulfonylureas and COX-2 inhibitors) and probably glitazones. There is significant interference in cardioprotection between sevoflurane and propofol, which should not be used concomitantly during anesthesia if possible. Any type of ischemic “conditioning” appears to exhibit markedly reduced protection or completely loses protection in the presence of volatile anesthetics and/or opioids.
Keywords: Anesthetics